Estrategias de arquitectura ecológica con bambú y el confort térmico en el Parque Nacional del Manu, Cusco - Cerron Oyague, Tania Miluska (2016)
This thesis develops architectural ecological strategies using bamboo and thermal comfort at the Manu National Park, Cusco, specifically for Section I of the Damping Area. The study chooses bamboo as main component to propose ecological architectural strategies that would help the conservation of a Natural Protected Area of worldwide importance such as the Manu National Park, because of its multiple contributions in environmental, economical and social aspects, and because it is a significant part of the native species of the Guadua genus in the Peruvian Amazon. The Manu -mainly the Damping Area- is currently affected by the human action, aggravated by the climate change effects and the financial-residential needs of the population. These strategies contemplate the thermal comfort of the people that would live in this environment, with minimal use of the energy, in the case of the study. Two main axes that have been taken into consideration in order to design the strategies are: the Natural physical environment and the Use of bamboo, with the selection of three local species, a native one of the Guadua genus, and two exotical ones of the Bambusa and Dendrocalamus genus. Plus, we’ve considered the Design and Construction. Each of these components and phases are related and we propose at the same time, an integral correlation between all of them. These strategies are applied with the execution of the Architectural Model - Bamboo Shack, which is validated by the population. The thermal conditions are estimated taking as a representative sample the evaluation of one of the rooms, an environment with natural ventilation, to be compared to the thermal conditions of a local building, with similar characteristics in terms of ventilation, use of natural materials, and the sensation of the local people. To achieve this purpose, we propose and develop a system and process chain to collect and process data, using for the thermal predictions the virtual simulator CBE Thermal Comfort Tool - standard ASHRAE 55, with its application: model PMV and adaptative model of comfort. The thermal estimate will be evaluated considering and applying appropriately, the guidelines of the first and second axes. In this way we manage to design, employ and validate strategies of architectural ecological bamboo and thermal comfort at the PNM, Manu, Cusco.